A revolutionary people at war : the Continental Army and American character, 1775-1783 - Royster, Charles (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 1979)
Discusses the role of the Revolutionary War--with its demands on courage, discipline, and dedication to the cause of freedom--on the shaping of America's national character.